Screening and identification of genes associated with flight muscle histolysis of the house cricket Acheta domesticus - Lu, Ying; Wang, Zizhuo; Lin, Fei; Ma, Yuqing; Kang, Jiangyan; Fu, Yuying; Huang, Minjia; Zhao, Zhuo; Zhang, Junjie; Chen, Qi; Ren, Bingzhong (Frontiers in Physiology, 2023)
Introduction: Flight muscle histolysis, as an important survival strategy, is a widespread phenomenon in insects and facilitates adaptation to the external environment in various insect taxa. However, the regulatory mechanism underlying this phenomenon in Orthoptera remains unknown. Methods: In this study, the flight muscle histolysis in the house cricket Acheta domesticus was investigated by transcriptomics and RNA interference. Results: The results showed that flight muscle histolysis in A. domesticus was standard and peaked within 9 days after eclosion of adult crickets, and there was no significant difference in the peak time or morphology of flight muscle histolysis between males and females. In addition, the differentially expressed genes between before and after flight muscle histolysis were studied, of which AdomFABP, AdomTroponin T and AdomActin were identified as candidate genes, and after injecting the dsRNA of these three candidates, only the downregulated expression of AdomFABP led to flight muscle histolysis in A. domesticus. Furthermore, the expression level of AdomFABP was compared between before and after flight muscle histolysis based on RT-qPCR. Disscussion: We speculated that AdomFABP might play a role in the degradation of flight muscle by inhibiting muscle development. Our findings laid a molecular foundation for understanding the flight muscle histolysis.